Three Variants Affecting Exon 1 of Ectodysplasin A Cause X-Linked Hypohidrotic Ectodermal Dysplasia: Clinical and Molecular Characteristics - Wang, Yupei; Zhang, Chuan; Zhou, Bingbo; Hui, Ling; Zheng, Lei; Chen, Xue; Wang, Shifan; Yang, Lan; Hao, Shengju; Zhang, Qinghua (Frontiers in Genetics, 2022)
Background Ectodysplasin A (EDA) variations are major pathogenic factors for hypohidrotic ectodermal dysplasia (HED), the most common form of ectodysplasin (ED), characterized by hypotrichosis, hypohidrosis, hypodontia, and other oral features. Methods Molecular genetic defects in three HED families were detected by whole-exome sequencing and confirmed by Sanger sequencing or multiplex ligation-dependent probe amplification. The effect of splicing variant was further verified by EDA minigene in vitro analysis. De novo deletion was confirmed by chromosomal microarray analysis. Results Three variants (c.396+1 G>C, c.171-173 del GTT, and exon 1 deletion) were identified, all affecting exon 1 of the EDA gene. Variants c.396+1 G>C and c.171-173 del GTT were first identified. Minigene analysis of the splicing variant (c.396+1 G>C) displayed a prolonged EDA-A1 transcript containing extra 699 bp at the start of intron 1, representing a functional cryptic splice site formation in vitro. Combining the results of chromosomal microarray analysis and whole-exome sequencing, the deletion variant was over 87 kb. Three variants were predicted to affect protein function to differing degrees, and were responsible for X-linked HED with varying phenotype. Conclusion Investigating the clinical and molecular characteristics of these variations broadens our understanding of EDA gene variants, supporting clinical diagnosis, genetic counseling, and prenatal diagnosis of HED.